The Distribution Pattern of Coffee Shop Public Spaces Based on Geographic Information System (GIS) in Majene Urban Area - Astinawaty, Astinawaty; Mukhlis, Jafar; Ahmadussaleh, Ahmadussaleh; Fauzan Ahmad, Muhammad (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2025)
The phenomenon of urban transformation in Majene through the development of coffee shop public spaces shows significant changes in the social, economic, and physical spatial structure of small cities in Indonesia. This study aims to : (1) identify the characteristics of coffee shops public spaces in Majene Urban Area, (2) analyze the distribution pattern of coffee shops public spaces in Majene Urban Area based on GIS. Methods used are quantitative descriptives statistics and GIS spatial analysis, namely buffer and Avarage Nearest Neighbor (ANN). The results of the study shows: (1) the characteristics of coffee shops public spaces is devided by two charachteristics: coffee shop and café, consist of 44 coffee shops and cafes in Majene Urban Area, spread across Banggae District and East Banggae District. East Banggae District in the area with the highest concentration of coffee shops 26 units and cafes 10 units. In Banggae District 6 unit coffee shop and 2 unit café, (2) the spatial distribution pattern of coffee shops public spaces is clustered with an ANN ratio of 0.655567 with an avarage real distance (observed mean distance) of 217.98 meters while the avarage expected distance (expected mean dstance) is 332.52 meters. The phenomenon of proxmity of one location to another is also supported by further statistcal results, namely a z-score value and p-value of -4.517352 and p-value of 0.000006. the highly negative z-score value and p-value far below the 0.05 threshold indicate high spatial significance and indicate that the distribution of coffee shops and cafes in Majene Urban Area is clustered and doesn’t randomly.